TINJAUAN YURIDIS INFORMED CONCENT BAGI PENANGANAN PASIEN GAWAT DARURAT - Oka Wijaya, I Komang Gede; Eka Wisanjaya, I Gede Pasek (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2014)
Paper titled “Judicial Review Of Informed Consent For Handling Emergency Patients. Informed consent an absolute requirement before doctor performed medical procedures to patients regulated on Article 8 of Law Act No. 36 Year 2009 Concerning Health and Article 45 Act No. 29 Year 2004 Concerning Practice of Medicine. Issues raised in this paper about the existence of informed consent exceptions for handling emergency patients Regulation Legislation in Indonesia. The purpose of this paper is determine the regulation of informed consent for handling emergency patients. The research method of this paper is normative research because conflict norm of informed consent as an absolute requirement difficult to applied for handling emergency patients. Informed consent can be waived for handling emergency patients on the Minister Regulation. 290/Menkes/Per/III/2008 and the explanation of Article 45 and Article 51 letter d Act No. 29 Year 2004 Concerning Medical Practice. That’s All for the sake patient and also the application of the principle of the protection and safety of patients on Act No. 36 Year 2009 Concerning Health and Act No. 29 Year 2004 Concerning Practice of Medicine.
Keywords: Informed Consent, Exception, Handling, Emergency